Pattern of gestational complications and low birth weight: a cross sectional study - Mahboob, Nabeela; Islam, Liza; Hossain, Ahmed (International Journal of Advances in Medicine, 2023)
Background: Complications of pregnancy and childbirth are the leading causes of disability and death among women of reproductive age in developing countries. The adverse events that occur during pregnancy influence the health of the child that may result in the neonatal outcome. Method: The analytical cross-sectional study was performed to assess the association between gestational complications and low birth weight (LBW) among woman of reproductive ages at Mohammadpur fertility services and training centre,100 bedded Mother and child health hospital in Dhaka city from January to March, 2018. After taking informed written consent, data was collected about gestational complication factors, socio-demographic factors and maternal factors through questionnaire and reviewing medical documents and data was analyzed in R software. Results: Out of total 400 live births, 114 (28.5%) babies were born with LBW. The results of the unadjusted analysis by the χ2 test indicate that sex of birth (boy or girl) (p≤0.001), household monthly income (p=0.004), preterm baby (p=0.005), duration of sleep hours (p=0.005) and mode of delivery (p=0.015), premature rupture of membrane (PROM) (p≤0.001), preterm labour (p=0.019), and overall maternal complications (p=0.004) are the significant variables to develop LBW among the mothers. Multivariable logistic regression model was fitted and stepwise regression was done. Conclusions: Despite government has taken many pragmatic steps, LBW is still prevailing in Bangladesh. Therefore, this study is expected to help government further to review their policies, strategies and recommendations pertaining to reduce LBW in Bangladesh.